2006
DOI: 10.1093/brain/awl163
|View full text |Cite
|
Sign up to set email alerts
|

Support for dopaminergic hypoactivity in restless legs syndrome: a PET study on D2-receptor binding

Abstract: Clinical observations support a central role of the dopamine system in restless legs syndrome (RLS) but previous imaging studies of striatal dopamine D2-receptors have yielded inconclusive results. Extrastriatal dopaminergic function has hitherto not been investigated. Sixteen RLS patients naïve to dopaminergic drugs and sixteen matched control subjects were examined with PET. [11C]Raclopride and [11C]FLB 457 were used to estimate D2-receptor availability in striatum and extrastriatal regions, respectively. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
2
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(170 citation statements)
references
References 88 publications
5
154
2
9
Order By: Relevance
“…27 While the symptoms of RLS may be attributed to alterations in spinal dopaminergic modulation, there is now pathologic and clinical evidence that patients with RLS also display changes in the striatonigral dopaminergic system, and the associative loop involved in decisionmaking. 28,29 Prior imaging studies in RLS have suggested either normal 30 or mildly impaired [31][32][33] presynaptic dopamine function, compatible to the findings reported here.…”
Section: Rlssupporting
confidence: 90%
“…27 While the symptoms of RLS may be attributed to alterations in spinal dopaminergic modulation, there is now pathologic and clinical evidence that patients with RLS also display changes in the striatonigral dopaminergic system, and the associative loop involved in decisionmaking. 28,29 Prior imaging studies in RLS have suggested either normal 30 or mildly impaired [31][32][33] presynaptic dopamine function, compatible to the findings reported here.…”
Section: Rlssupporting
confidence: 90%
“…11 C]SCH23390 and [ 11 C]FLB457 studies (Cervenka et al, 2006;Takahashi et al, 2008;Karlsson et al, 2009;McNab et al, 2009), a very small region or a single voxel is susceptible to partial volume effect. Thus, it is recommended that parametric image analysis should be used in combination with ROI analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients with MS, 71 (78%) had relapsingremitting MS (RRMS), 8 (8.8%) had secondary progressive MS (SPMS), 3 (3.3%) had progressive relapsing MS (PRMS), and 9 (9.9%) had primary progressive MS (PPMS). The median number of attacks was 3 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and the median EDSS score was 3 (0-9) in the MS group (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that hypoactive dopaminergic neurotransmission might contribute to the pathophysiology of RLS (9).…”
Section: Figurementioning
confidence: 99%